Untersuchungen über Fluor im Krill (Euphausia superba dana) - Christians, O.; Leinemann, M. (1980)
Johann Heinrich von Thunen-Institute, Federal Research Institute for Rural Areas, Forestry and Fisheries began publishing the Informationen aus der Fischereiforschung – Information on Fishery research in 2010